Analysis of student's misconceptions on the material of the immune system using a three-tier diagnostic test - Yemima Nestaria Nainggolan; Karunia Galih Permadani; Setiyo Prajoko (STKIP Persada Khatulistiwa Sintang, 2022)
Distance learning and face-to-face learning at Senior High School of 3 Magelang makes it difficult for students to understand the concept of the system the immune system so that it triggers misconceptions in students. This study aims to analyze students' misconceptions about the material on the immune system at Senior High School of 3 Magelang. The research method is uses qualitative methods to be able to explain more deeply about students' misconceptions. Twenty-five multiple-choice questions in three tiers are given to determine the distribution of students' conceptions. The analysis showed that 64,16% of misconceptions were found in the concept of definition and function of the immune system, followed by the concept of antigens and antibodies with 58.7%, the concept of the mechanism of the immune system with 56.74% and disorders of the immune system with 41.4%. Based on the interviews and questionnaires, the factors that cause misconceptions come from the teacher's teaching methods with less effective, text-books and the lack of student activity, and learning media that have not been varied. So, it can be concluded that students' misconceptions on the material of the immune system are still found with a high level of misconceptions.